The Ratification of Omnibus Law: A Sign of Democratic Deconsolidation in Indonesia - Muchamad Zaenal Arifin; Wahyu Budi Nugroho; Ana María Naranjo Cortés; Pricilia Purnama (JSW (Jurnal Sosiologi Walisongo), 2022)
Indonesia as a post-authoritarian democratic country has made impressive progress in its democratic transition. However, there is a significant contradiction in the democratic process, particularly in policy and law-making. This study aims to discuss democratic deconsolidation contributing to the ratification of the Omnibus Law on Job Creation in Indonesia. Applying the qualitative method by using academic literature, news analysis, and official government documents, the first research finding shows that the accumulation of Joko Widodo's political power has affected the quality of debate and the agreement during the deliberation of the Omnibus Law in the parliament. Secondly, the opaque process limiting public participation has narrowed the space for the democratic mobilization of the citizens. Thirdly, the increasing number of retired armed forces in domestic affairs has resulted in the dual function of military power in securing the country and the economic development agenda. The study shows that the deconsolidation of democracy has contributed to the ratification of the Omnibus Law on Job Creation which was deliberated through a non-transparent mechanism.